BC047440 antisense eukaryotic expression vectors inhibited HepG2 cell proliferation and suppressed xenograft tumorigenicity - Zheng,Lu (2012)
The biological functions of the BC047440 gene highly expressed by hepatocellular carcinoma (HCC) are unknown. The objective of this study was to reconstruct antisense eukaryotic expression vectors of the gene for inhibiting HepG2 cell proliferation and suppressing their xenograft tumorigenicity. The full-length BC047440 cDNA was cloned from human primary HCC by RT-PCR. BC047440 gene fragments were ligated with pMD18-T simple vectors and subsequent pcDNA3.1(+) plasmids to construct the recombinant antisense eukaryotic vector pcDNA3.1(+)BC047440AS. The endogenous BC047440 mRNA abundance in target gene-transfected, vector-transfected and naive HepG2 cells was semiquantitatively analyzed by RT-PCR and cell proliferation was measured by the MTT assay. Cell cycle distribution and apoptosis were profiled by flow cytometry. The in vivo xenograft experiment was performed on nude mice to examine the effects of antisense vector on tumorigenicity. BC047440 cDNA fragments were reversely inserted into pcDNA3.1(+) plasmids. The antisense vector significantly reduced the endogenous BC047440 mRNA abundance by 41% in HepG2 cells and inhibited their proliferation in vitro (P < 0.01). More cells were arrested by the antisense vector at the G1 phase in an apoptosis-independent manner (P = 0.014). Additionally, transfection with pcDNA3.1(+)BC047440AS significantly reduced the xenograft tumorigenicity in nude mice. As a novel cell cycle regulator associated with HCC, the BC047440 gene was involved in cell proliferation in vitro and xenograft tumorigenicity in vivo through apoptosis-independent mechanisms.